Directions of changes taking place in polish public administration - Bojar-Fijałkowski, T. (Право и государство, 2017)
With social, civilizational and economic development, the needs and expectations of societies towards the state and its bodies, especially the public administration, are changing. Simultaneously, the tendencies for changes come from the public administration itself and its personnel. Not without significance for model of public administration is the political, social and economic doctrine, which may favor greater or less involvement of the state and thus the public administration into the life of citizens. After all, in Poland’s case, some changes are necessary due to European Union membership, which with respects the principle of procedural autonomy of states, is giving guidance to the public administrations of the Member States, such as soft law standards or the jurisdiction of the Court of Justice of the European Union. All this is aimed at realizing the right to a good administration and causes that the public administration in Poland is dynamic. Because it is worth watching, learning from others, sometimes drawing critical conclusions, sometimes motivating, this text is supposed to present to the reader directions of changes taking place in the Polish public administration.Hence the layout of this study, which begins with the theoretical part explaining the notion of public administration on the grounds of Polish legal doctrine. The second part is devoted to new ideas and theoretical concepts of public administration, which begin to be implemented in Poland. Next part refers to the process of state withdrawal, thereby and the public administration, from the activity in public sector, for example in environmental protection. The fourth part deals with the replacement of public entities, including administration, by private entities in the implementation of public services, for example in the communal services. The fifth part, the last one, describes currently implemented proces of computerization of activity in public administration, administrative proceedings and court-administrative proceedings in Poland. The study ends with the conclusions and the list of sources.The work was based on sources of, widely understood, administrative law and administrative science, as well as legal acts current as of August 31, 2017.
Keywords: public administration; new public management; new public management; com- puterization; Poland; European Union; Research Subject Categories::LAW/JURISPRUDENCE